51-Chromiumethylenediaminetetraacetic acid (51Cr-EDTA) glomerular filtration Rate (GFR) analysis: comparing two blood sampling with multiple blood sampling - Abdul Rahim, Mohamad Shahrir (2015)
The glomerular filtration rate (GFR) is the commonest method used to quantify renal function. Chromium-51-Ethylenediaminetetraaceticacid (51Cr-EDTA) plasma clearance has been accepted as a gold standard method in measuring GFR. Several methods have been proposed in which the glomerular filtration rate is estimated from using only one or two blood samples to using multiple blood samples. The purpose of this study is to determine the accuracy of using two blood samples compared to multiple blood samples, for calculation of GFR by the 51Cr-EDTA method. In addition, the study aimed to determine the best combination time of two blood sampling and correlation with gender and ethnicity of the patients. 51Cr-EDTA tracer solution is injected into a vein in the upper arm. Six mls of whole blood is then drawn from the opposite arm at 120, 150, 180 and 240 minutes, centrifuged and 2 ml aliquots of plasma are pipetted and counted for a period of 5 minute each time, in an automatic gamma well counter. GFR is calculated by measuring Cr-EDTA plasma clearance using slope intercept method. The patients’ height and weight is used to correct the GFR to body surface area. Correlations of the values are tested by Pearson and Intraclass correlation, and mean and standard deviation derived from pair t-test. All time point combinations using two blood sampling shows a high correlation with multiple blood sampling method (p value < 0.001, r = 0.909 to 0.989). The best combination using two blood sampling is at 2 and 4 hour time point (r = 0.989 with 99% consistency). 51Cr-EDTA GFR estimation using two blood sampling method is accurate and reliable. The two and four hour time point is found to be the best. Gender and ethnicity does not influence GFR estimation using two blood sampling method.